Penyelesaian Perselisihan Pemutusan Hubungan Kerja secara Bipartit berdasarkan Undang-Undang Nomor 2 Tahun 2004 (Neolectura, 2022)
The problems that occur in the world of work are not only workers and the availability of jobs. The problem of termination of employment or layoffs is one of the problems that often occurs. Differences in perceptions regarding layoff decisions made by employers or workers give rise to disputes. This dispute certainly disrupts the company's operations so it needs to be resolved quickly and fairly for all parties. The state as the protector of society regulates the bipartite settlement of layoff disputes. The purpose of this research is to find out the bipartite dismissal dispute settlement mechanism based on UU No 2 Tahun 2004. This juridical research obtained data from literature, regulations, and laws related to this study. The study show the bipartite negotiation mechanism, namely the stages before the negotiations, bipartite negotiations, minutes of negotiations, and reporting of the minutes of bipartite negotiations.